Energy Security and the Future of Development in Africa - Asuelime, Lucky E.; Simura, Blessing (Palgrave Macmillan, 2021)
African development has become a major discussion issue both in and outside Africa. The continent is seen as the new and rising destination for capital and investment. It has seen both the financially rich Eastern and Western bloc of nations competing for African attention. However, this development rush is not uniform across the whole continent, given that Africa is made up of 54 countries that have different levels of enabling environments and varied developmental strides. The major element that is critical for development both in social and business terms is energy security. The main thrust of this chapter is to argue that for Africa to take off and compete with other emerging economies there is need for massive investment in the energy sector.